(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
The popularity of the road film in the 1970s is often attributed to its updating of the Western film genre, an enduring form in Hollywood cinema. This essay argues that a hierarchical understanding of the relationship between the two genres is detrimental to understanding their efficacy. Case studies of two minor films produced outside of the Hollywood studio system reveals the centrality of landscape and spatiality to generic evolution. While the mythology of New Hollywood Cinema touted a reflexive deployment of genres that perpetuated in Hollywood for most of the studio era, these independently produced films endeavored to imagine an alternative to this ideologically dominant system. This article explores the uneasy balance of subversion and citation of genre to gain an understanding of the complex relationship between authorship, production, and hegemonic practices in this transitional era of American film history.